2018
DOI: 10.1002/elps.201800020
|View full text |Cite
|
Sign up to set email alerts
|

Use of Endoglycosidase H as a diagnostic tool for MAN1B1‐CDG patients

Abstract: Congenital disorders of glycosylation (CDG) are heterogeneous group of genetic protein and lipid glycosylation abnormalities. With some 33 reported patients, MAN1B1‐CDG belongs to the more frequent causes of CDG‐II. MAN1B1 encodes an α1,2‐mannosidase that removes the terminal mannose residue from the middle branch. Several methods have been proposed to characterize the glycosylation changes. In MAN1B1‐CDG, the abnormal accumulating N‐glycan structures are mostly absent or found in trace amounts in total human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Although specific, those N-glycan species occur at trace levels in serum (<10% when summing all the PNGase-released species), which corroborates the intriguing involvement of a limited number of circulating N-glycoproteins. By hydrolyzing Endo H-released N-glycans with mannosidases, Duvet et al demonstrated that MAN1B1-specific hybrid N-glycans have isomeric structures different from those present in control samples, with α1,2 linked mannose residues [ 10 ]. Recently an alternative MS-based strategy involving the analysis of Rapifluor-derivatized PNGase F-released N-glycans, Messina et al [ 17 ] confirmed these findings in MAN1B1-CDG individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although specific, those N-glycan species occur at trace levels in serum (<10% when summing all the PNGase-released species), which corroborates the intriguing involvement of a limited number of circulating N-glycoproteins. By hydrolyzing Endo H-released N-glycans with mannosidases, Duvet et al demonstrated that MAN1B1-specific hybrid N-glycans have isomeric structures different from those present in control samples, with α1,2 linked mannose residues [ 10 ]. Recently an alternative MS-based strategy involving the analysis of Rapifluor-derivatized PNGase F-released N-glycans, Messina et al [ 17 ] confirmed these findings in MAN1B1-CDG individuals.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these drawbacks, alternative strategies (more or less accessible in clinical settings) have been proposed such as targeted analysis of immunopurified Trf and/or IgG [ 4 , 9 ] as well as the convenient detection of high-mannose and hybrid-type N-glycans following Endo-β- N -acetylglucosaminidase (Endo H) serum treatment. Indeed, Duvet et al [ 10 ] reported unambiguous profiles of Endo H-released serum N-glycans for seven MAN1B1-CDG patients with clear accumulation of oligosaccharidic structures harboring 4–5 Man residues.…”
Section: Introductionmentioning
confidence: 99%
“…N ‐glycans were prepared and released by PNGase F from an aliquot of 20 μL of serum as previously described 17 . Released glycans were then permethylated, extracted and purified on a Sep‐Pak column as previously described 18 .…”
Section: Methodsmentioning
confidence: 99%
“…Early in 2013, MALDI-TOF/TOF (Applied Biosystems 4800) was applied to profile the permethylated glycans derived from congenital disorders of glycosylation (CDGs) patient sera and proved to be able to differentiate CDG from controls ( Xia et al, 2013 ). Recently, Duvet et al (2018) investigated the serum N-glycome expressions in MAN1B1-CDG patients using the same MAIDI-TOF/TOF system in combination with an Endo-β-N-acetylglucosaminidase H (Endo H) digestion. Since the Endo H can only release high-mannose and hybrid structures, a straightforward investigation of MAN1B1 deficit was achieved.…”
Section: Mass Spectrometry-based Separation Techniques Facilitate Gly...mentioning
confidence: 99%